Novel energy-based rational for nominal ductility design of very-high strength concrete columns (>100 MPa). (1st November 2019) - Kristombu Baduge, Shanaka; Mendis, Priyan
Highlights: Analytical program used to predict energy ductility of Very-High Strength Concrete (VHSC) columns. New Energy-based ductility indices are proposed for VHSC columns. A novel energy-based nominal ductility design method is proposed. Proposed approach reduces the lateral steel and enables using VHSC columns. Abstract: Ductility forewarns the failure and enables a structure to undergo large deformation while sustaining load carrying capacity and dissipate energy in an earthquake event. Considering recent advances in energy-based seismic design approach, presenting a novel energy-based ductility design approach for nominal ductility design of VHSC (>100 MPa) columns while considering the higher plastic energy within the VHSC columns is the focus of the study. In this paper, an accurate program to predict analytical full-range moment-curvature relation using appropriate stress-strain behavior of constitutive materials is used to predict the energy-based and curvature ductility of rectangular VHSC columns including possible failure mechanisms. Considering deficiencies in existing ductility indices for VHSC, the study proposes energy-based ductility indices and discusses the suitability for nominal ductility design. The threshold for nominal ductility design of a VHSC column is proposed as the flexural rotation-based energy ductility level ( Eθ ) of a similar 50 MPa concrete column which is a similar approach to the nominal ductility design method in the Australian Concrete Structures Standard, AS 3600 [1]. It showed that the new approach reduces the required amount of confinement steel because the new index can represent the increase of energy ductility of VHSC columns accurately, at higher axial load levels and higher strengths. Using this approach practical amount of lateral steel and spacing can be suggested for rectangular VHSC columns with compressive strengths up to 150 MPa which enables the use and economical designs of VHSC for nominal ductile structures.